Effect of Acetylsalicylic Acid Treatment on Gait Score and Femur Osteometry in Broiler Chickens - Gungoren, Gulsah; Demırcıoglu, Ismaıl; Sımsek, Ülkü Gülcıhan; Keskinbıçak, Yakup; Akarsu, Selçukhan; Kanik, Betül (My University, 2024)
The current research examined the effects of adding 0.03%, 0.06%, 0.1%, 0.3%, and 0.6% acetylsalicylic acid (ASA) to drinking water between 24 and 45 days on gait score and femur osteometry. The gait score average of the birds slaughtered on the 49th day was above 3, and no difference was found between the groups. It was determined that ASA treatment did not affect the osteometric and index values of the femur bones taken and examined after slaughter. In conclusion, it was concluded that ASA was not effective in preventing skeletal deformations caused by rapid growth in broilers.
Keywords: Femur; Welfare; Acetylsalicylic acid; Rapid growth